2016
DOI: 10.5455/sad.13-1477551776
|View full text |Cite
|
Sign up to set email alerts
|

The Opinion Of The Nurses Working In The Hospitals About The Electronic Medical Records They Use: Sanliurfa Example

Abstract: ÖZETBu araştırma hastanelerin kliniklerinde çalışan hemşirelerin, hastanede kullandıkları elektronik tıbbi kayıtlara ilişkin görüşlerinin kullanım, kalite ve kullanıcı tatmini açısından değerlendirmesini yapmaktır. Araştırma, anket esasına dayalı bir alan araştırmasıdır. Araştırma Şanlıurfa ili merkezinde bulunan Harran Üniversitesi Hastanesi ile Özel Edessa hastanesinin kliniklerinde çalışan hemşirelere yapılmıştır. Araştırmada, hastanelerin kliniklerinde çalışan 115 hemşirenin 93'üne anket uygulanmıştır. Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
4
0
4
Order By: Relevance
“…In the study carried out by Top and Gider, significant correlations were found among use, quality and user satisfaction scores, and they determined that the highest correlation was between quality and user satisfaction scores for EMR systems . Likewise, in the study carried out by Eriş, it was found that the relationship between quality and satisfaction was high …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the study carried out by Top and Gider, significant correlations were found among use, quality and user satisfaction scores, and they determined that the highest correlation was between quality and user satisfaction scores for EMR systems . Likewise, in the study carried out by Eriş, it was found that the relationship between quality and satisfaction was high …”
Section: Discussionmentioning
confidence: 96%
“…It was found in the study performed by Cinaroglu and Avcı in 2015 regarding internal diseases and surgical nurses that the general average views of nurses on the use of electronic health records were scored as 1.39 . In the study carried out by Eriş, the score of nurses for the use of EMRs and the assessment score of nurses for the quality of EMRs were found as 3.59, and their user satisfaction level for EMRs was found as 3.23 . Asiri et al reported that nurses had positive attitudes regarding the use of EMRs and thought that EMRs were useful in supporting clinical practices .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teknolojinin hemşirelerin iş yüküne etkisi 9 çalışmada ele alınmıştır (Bilgiç ve Özdemir Aydın, 2015;Dikmen, Ak ve Yorgun, 2015;Aydoğan ve ark., 2016;Çakır Umar, Öğce, Yavuz Van Giersbergen, ve Karaveli Çakır, 2016;Çakırlar ve Mendi, 2016;Eriş, 2016;Karadağlı ve Genç, 2017;Terkeş, Çelik, Taşdelen ve Kılıç, 2018;Tiryaki, Zengin ve Çınar, 2018). Bilgiç ve Özdemir Aydın'ın (2015) 60 hemşire ile yaptığı çalışmada hemşirelerin %81,7'si, bilişim teknolojilerini kullanmanın işlerini hızlandırdığını ve kolaylaştırdığını belirtmişlerdir.…”
Section: Teknolojinin Hemşirelik Mesleğinde İş Yükü Ve Bakım Kalitesine Etkisiunclassified
“…Hemşireler bakımı planlanma ve uygulamada bilgisayar temelli bakım süreci kullanmakta, sağlık sistemindeki tüm birimlerde elektronik tıbbi kayıt sisteminde bilgisayar ve farklı yazılım sistemleri kullanılmakta, bilgiye ulaşmada ve ekipler arası iletişimi sağlamada yine bilgisayar ve akıllı telefonlar gibi teknolojik cihazlar hemşireler tarafından kullanılmaktadır. Hemşirelik öğrencileri açısından baktığımızda ise bilgiye ulaşmada bilgisayar ve akıllı telefonlar gibi teknolojik cihazlar, eğitimde ise bilgisayar, internet, web tabanlı yazılımlar ve simülasyon eğitim yöntemi kullanılmaktadır (Aydoğan Sayar, Gülhan ve Yılmaz, 2016;Eriş, 2016;Şenyuva, 2017b;Tatlı ve ark., 2018;Ünsal Atan ve ark., 2019).…”
Section: Introductionunclassified